Day-ahead wind-thermal unit commitment considering historical virtual wind power data. (15th November 2021) - Dong, Jizhe; Han, Shunjie; Shao, Xiangxin; Tang, Like; Chen, Renhui; Wu, Longfei; Zheng, Cunlong; Li, Zonghao; Li, Haolin
Abstract: The uncertainty in wind power affects the generation scheduling (unit commitment) of coal-dominated power systems. A reasonable spinning reserve is required to handle this uncertainty. In this study, a method that considers the unique local wind regime into the calculation of spinning reserve requirements and makes the unit commitment more local-adaptive is presented. First, a virtual wind power transfer matrix which displays the probabilities of wind power transferring from one value to another by using the historical wind speed data is formulated. Second, the spinning reserve requirements of the wind-thermal power system are calculated according to the virtual wind power transfer matrix. Finally, the day-ahead unit commitment is conducted based on the spinning reserve calculation. The main advantage of using historical virtual wind power data, instead of historical wind speed data, is the acquisition of real wind power transfer probabilities, which avoids the distortion caused by the nonlinear conversion between wind power and wind speed. Application and comparison studies to demonstrate the effectiveness and cost benefits are performed on two systems. Sensitivity analyses of different parameters used in the method are also investigated. Graphical abstract: Image 1 Highlights: A modified wind-thermal unit commitment model is proposed. Wind power transfer matrix is formed to include the local wind characteristics. Additional spinning reserve is calculated using the wind power transfer matrix. Comparison study is conducted. More realistic result with lower operating cost can be obtained.